Disenchanting Albert the Great: the life and afterlife of a medieval magician - Collins, David J. (The magic in history series, 2024)
"Examines the life and work of the medieval friar and magician Albert the Great, using his disputed reputation as a case study for the complex history of magic and its connection with science and religion"--